Analysis Of Factors Influencing Students’ Intention To Use E-Wallets In Payment Transactions - Juliana, Pinti; Soleh, Ahmad; Abi, Yudi Irawan (Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
This study aims to analyze and explain the influence of usefulness, ease of use, security, and trust factors on students’ interest in using e-wallets as a digital financial transaction tool. E-wallets represent an innovation in modern payment systems that provide convenience and efficiency for users, particularly among young generations who are familiar with technology. This research employed a quantitative approach with a survey method by distributing questionnaires to 129 respondents, consisting of students from the Faculty of Economics and Business, Universitas Dehasen Bengkulu, class of 2022. The collected data were processed and analyzed using multiple linear regression analysis with the assistance of SPSS version 31.0 (2025). The analysis was conducted to examine both the partial and simultaneous effects of the independent variables on the dependent variable, namely students’ interest in using e-wallets. The results of the study show that the factors of usefulness, ease of use, and trust have a positive and significant effect on students’ interest in using e-wallets. This means that the higher the level of perceived usefulness, convenience, and trust, the greater the students’ interest in utilizing e-wallets for their daily transactions. Conversely, the security factor does not have a significant effect, indicating that students have not placed security as a primary consideration in using e-wallets. Overall, the four factors simultaneously influence students’ interest, with trust being the most dominant variable. These findings illustrate that students of Universitas Dehasen Bengkulu, class of 2022, place greater emphasis on the aspects of usefulness, ease of use, and trust rather than security when deciding to use e-wallets as a modern digital payment method.